Intestinal Microbiota Dysbiosis Disrupts the Mucosal Barrier, Triggering Inflammatory Responses in Gut-Kidney Interaction and Exacerbating Diarrhea - Shen J; Fang L; Wu Y; Deng N; Peng X; Li D; Tan Z (Journal of Inflammation Research)
Junxi Shen,1,2 Leyao Fang,1,2 Yi Wu,1,2 Na Deng,1,2 Xinxin Peng,2,3 Dandan Li,1,2 Zhoujin Tan1,2 1School of Traditional Chinese Medicine, Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of China; 2Hunan Key Laboratory of Traditional Chinese Medicine Prescription and Syndromes Translational Medicine, Changsha, Hunan, People’s Republic of China; 3The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Zhoujin Tan, Email tanzhjin@sohu.com Dandan Li, Email 48797696@qq.comPurpose: Intestinal microbiota dysbiosis is observed in diarrhea with kidney-yang deficiency syndrome. Therefore, this study will explore the mechanisms by which intestinal microbiota dysbiosis contributes to the initiation and progression of this condition.Methods: Thirty SPF-grade male KM mice were randomly assigned to three groups: the control group, the diarrhea with kidney-yang deficiency syndrome model group, and the intestinal microbiota dysbiosis + diarrhea with kidney-yang deficiency syndrome model group. After the modeling period, samples were collected. HE staining was employed to observe pathological changes in the colon and kidneys. Detect and analyze the functions of the colonic mucosal barrier and renal function. Measure the levels of NOD-like receptor family pyrin domain containing protein 3 (NLRP3) inflammasome-related molecules and inflammatory factors in the colon and kidney tissues. 16S rRNA sequencing combined with bioinformatics analysis was employed to evaluate the diversity and species composition of the intestinal microbiota, conduct correlation analysis, and predict its metabolic functions.Results: The model mice exhibited increased fecal water content and decreased body temperature. Structural damage was observed in both the colon and kidney tissues. The intestinal mucosal barrier function was impaired. Furthermore, elevated levels of NLRP3 inflammasome-related molecules and inflammatory cytokines were observed in both colon and kidney tissues. Additionally, alterations were noted in the microbial community structure of the colon contents, characterized by decreased richness, diversity, and evenness. Finally, correlation analysis revealed a significant positive correlation between the characteristic bacterium Phocaeicola_A and NLRP3, IL-1β, and IL-18 in both colon and kidney tissues.Conclusion: Intestinal microbiota dysbiosis leads to a decline in intestinal mucosal barrier function, accompanied by inflammatory responses and pathological changes in both colonic and renal tissues, resulting in gut-kidney interaction damage. Collectively, these changes promote the development of diarrhea with kidney-yang deficiency syndrome.Keywords: diarrhea, dysbiosis, gut-kidney interaction, inflammation, intestinal microbiota